The assessment of environment of care in Hospital USM through in-patient satisfaction survey and ward rating audit - Zun, Ahmad Badruridzwanullah (2021)
The assessment of environment of care in Hospital USM through in-patient satisfaction survey and ward rating audit validity. The field testing process for HCAHPS Malay version was conducted among 200 discharged patients from Hospital USM. In part two, there were two surveys conducted, first, in-patient satisfaction survey that involved 547 discharged patients in determining the patient perception on EoC, patient satisfaction level and its associated factor. Second, the ward rating audit survey as an objective assessment of physical EoC was conducted concurrently with an in-patient satisfaction survey involving 13 wards. Result: The overall content validation index (CVI) was calculated to be 0.87 and iCVI for individual items ranged from 0.8 to 1.0. The face validity index (FVI) of clarity and comprehension were 0.83 and 0.82, respectively, and the FVI universal was 0.82. For construct validity, the factor loading ranging from 0.652 to 0.961 within nine domains. The overall Cronbach alpha for the HCAHPS-Malay version was determined to be 0.84 and values for each domain ranging from 0.69 to 0.93. About three fifth of respondents were satisfied with hospital services. About 15.4% to 36.9% of the patients have positive perception level in all EoC domains. The income level of the patient and doctor–patient communication domain was significantly associated with satisfaction level with (adj. OR = 0.38; 95% CI 0.17,0.88; P =0.023) and (adj. OR = 3.23; 95% CI: 2.01, 5.19; p < 0.001) respectively. The perception score for the physical EoC comprised of cleanliness of the hospital environment was 3.11 (+ 0.94) while quietness of the hospital environment was 2.52 (+1.24). For objective measure of physical EoC, compliance of infection control had the highest mean score (4.42 + 0.40) while physical cleanliness and patient safety domain shared the lowest mean score with 3.92 + 0.51 and 3.92 + 0.83 respectively. There was a positive correlation between the perception of cleanliness and an objective measure of a cleanliness of environment (r=0.08, p value <0.05), safe environment (r= 0.14, p value <0.01), and conducive environment (r = 0.11, p value <0.01). Conclusion: This study provides an opportunity for improvement of EoC in Hospital USM especially on the social EoC as the proportion of positive perception among patient was considered low and the domain on communication with doctor was associated with low satisfaction level. Besides that, the physical EoC also need to be improved since it can be closely related with hospital infectious control and patient safety.